Pengembangan Media Game Based Learning Berbasis Ecoliteracy Untuk Meningkatkan Pemahaman Konsep Pada Materi Sumber Daya Alam Siswa Kelas IV SD - sofa, Kharisma Salsabila Sofa; Wahyuningsih, Yona; Nanggala, Agil (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2026)
Natural resource learning in elementary schools is still not optimal and tends to be memorization based, resulting in low conceptual understanding and limited awareness of natural resources in daily life. This study aims to develop an ecoliteracy based game based learning media to improve students conceptual understanding. The research employed Design and Development (D&D) type 1 using expert validation questionnaires, user response questionnaires, and multiple choice tests. The results showed that the media was highly feasible with expert validation of 95% and user response of 92.48%. The data were normally distributed (Sig. 0.722), and the t-test indicated a significant improvement (Sig. <0.001). the N-Gain score was 0.68 (moderate). Therefore, the Buminesia media is effective and can be used as an alternative learning resource in elementary science learning.